POLAND’S “EASTERN POLICY”: FROM “UKRAINE, LITHUANIA, BELARUS” TO THE «EASTERN PARTNERSHIP» - Anna V. Chernova (Vestnik MGIMO-Universiteta)
The article deals with the evolution of Poland’s foreign policy towards its closest eastern neighbours: independent Ukraine, Lithuania and Belarus. It’s commonly referred to in the Polish historical science as the “Eastern Policy” and the countries themselves as the “Eastern outskirts” as opposed to the classical western understanding of “the East”, for which the Latin word “Orient” is used. Throughout Poland’s history this region was of a prominent role, at times being a part of the Polish-Lithuanian Commonwealth and at other times some kind of a “no-man’s land”, while taking its current shape only after the USSR and the Eastern block collapse.Though Russia is often considered to be a part of Poland’s “Eastern Policy”, the difference is clear in the nature of relationship between Warsaw and Moscow and that of the “ULB” (Ukraine, Lithuania and Belarus). In addition, Poland’s area of responsibility as an EU member included Ukraine and Belarus rather than Russia, which predominantly remained a priority of the “old” EU member states. Therefore the Russian-Polish relations figure here as a background, while the focus is on the “ULB” states. Increasing integration of the Polish “Eastern Policy” into the EU’s framework necessitated touching upon Moldova as well as Armenia, Azerbaijan and Georgia, which were invited along with Ukraine and Belarus to participate in a major European initiative– the “Eastern Partnership”. For the same reason two phases were outlined: before and after Poland’s accession to the EU which formally took place on 1st of May, 2004.